A new group of anti-lipopolysaccharide factors from Marsupenaeus japonicus functions in antibacterial response. Issue 1 (January 2015) - Jiang, Hai-Shan; Zhang, Qing; Zhao, Yan-Ran; Jia, Wen-Ming; Zhao, Xiao-Fan; Wang, Jin-Xing
Highlights: A new group of ALFs (MjALF-E1 and E2) was identified in Marsupenaeus japonicus . Both Mj ALF-E1 and E2 were upregulated by G + and G − bacterial challenge. Mj ALF-E1 and E2 strongly bind to bacterial cell wall components LPS and PGN. Mj ALF-E2 exhibited antimicrobial activity against Gram-negative bacteria. Mj ALF-E2 promotes the clearance of bacteria in shrimp. Abstract: Anti-lipopolysaccharide factors (ALFs) are a group of critical effector molecules with a broad spectrum of antimicrobial activities in crustaceans. Four groups of ALFs (A, B, C, and D) have been identified in peneaid shrimp. In the study, we identified a new group of ALFs (designated as Mj ALF-E) from Marsupenaeus japonicus . This new group (group E) included Mj ALF-E1 and E2. Mj ALF-E1 was highly expressed in hemocytes, heart, and intestine, whereas E2 was highly expressed in gills, stomach, and intestine. Expressions of both Mj ALF-E1 and E2 were upregulated by bacterial challenge. Synthesized LPS-binding domain peptides of Mj ALF-E1 and E2 strongly bind to bacterial cell wall components lipopolysaccharide (LPS) and peptidoglycan (PGN). The recombinant r Mj ALF-E2 showed relatively weak binding activity to LPS and PGN. Both synthesized peptides and r Mj ALF-E2 exhibited antimicrobial activity against Gram-negative bacteria, whereas r Mj ALF-E2 could promote the clearance of bacteria in vivo. After knockdown of Mj ALF-E2 and infection with Vibrio anguillarum, shrimp showed high and rapid mortality compared with GFPi shrimp. These results suggest that Mj ALF-Es serves a protective function against bacterial infection in shrimp.